Harvesting Knowledge: Illuminating Advances in Brassica Crops Genomics and Breeding - Xu Cai; Jian Wu; Xiaowu Wang (Horticulturae, 2023)
Brassica crops encompass a diverse array, including vegetables, oil crops, ornamentals, and condiments [...]